Training of Fertilizer Application Methods For Coffee Farmers in Gampong Paya Guci, Tangse District - Muliana, Muliana; Syafri, Yulia; Yusra, Yusra (Jurnal Malikussaleh Mengabdi, 2023)
Paya Guci is a village located in Tangse District, Pidie District, Aceh Province. 75% of the population's livelihood as farmers. Tangse became the center for Liberika coffee (kupi panah) in Aceh. Liberika coffee the early 19th century was brought to Tangse by the Dutch. One of the factors to support crop productivity is through fertilization, but the Gampong Paya coffee farmers have relatively never fertilized their coffee plants. Therefore, we need "Training of Fertilizer Application Methods for People's Panah Coffee Plants in Gampong Paya Guci, Tangse District, Pidie Regency". The aim is to transfer knowledge and skills on how to fertilize coffee properly. The method used in this service is counseling and training. The activity was carried out in two stages. The result of the service activity was that the extension activity was attended by 61 participants (members of farmer groups and community leaders). The community advocacy team assists and teaches community leaders and farmer group leaders in carrying out fertilization practices directly on farmers' kupi panah plants. Community leaders and farmer groups asked the Unimal service team: (1) the Unimal service team became the coach and companion of farmer groups in Paya Guci on an ongoing basis, (2) the Unimal service team in the future checked the soil pH of the Paya farmer's farmland jars so liming and fertilizing can be carried out according to soil conditions, (3) the Unimal service team is then willing to become a companion for the formation of farmer group cooperatives. Simultaneously with this dedication activity, there was also a signing Memorandum off Understanding (MOU) document between Unimal and Gampong Paya Guci